ANALISIS PERBAIKAN PERGESERAN DINDING CONTIGUOUS BORED PILE DENGAN PERMODELAN PLAXIS V 8.2 STUDI KASUS : PROYEK PEMBANGUNAN BASEMENT CIPUTRA INTERNATIONAL PHASE 1 - Irma Sepriyanna; Wendy Frayoga Damanik (Sekolah Tinggi Teknik - PLN, 2016)
Fewer land available, making the switch to vertical development with lots of built high-rise building toreplace the buildings that wide. One of the facilities must be put in a tall building is the parking of vehicles.Park is prepared to meet the demands of a large parking area and safely placed in the basement or abasement parking. Based on analysis of the shift, strain, stress, axial force, shear force, force moment and thesafety factor (safety factor) wall contiguous bored pile, which then calculate the design strength of anchorand length of anchor needed to repair the shift to development projects basement Ciputra International Phase1 improvements obtained shift condition 2 (excavation 1) a maximum of 1.65 m, the voltage -480.56 kN / m,strain 261.16% -147.04 wall axial force kN / m, -80.304 shear force kN / m, the moment of the KNM -180.01 /m and a safety factor 4.7650.